2015
DOI: 10.1152/ajprenal.00601.2014
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glomerulotubular balance. III. Implication of cytosolic calcium in flow-dependent proximal tubule transport

Abstract: In the proximal tubule, axial flow (drag on brush-border microvilli) stimulates Na ϩ and HCO 3 Ϫ reabsorption by modulating both Na/H exchanger 3 (NHE3) and HATPase activity, a process critical to glomerulotubular balance. We have also demonstrated that blocking the angiotensin II receptor decreases baseline transport, but preserves the flow effect; dopamine leaves baseline fluxes intact, but abrogates the flow effect. In the current work, we provide evidence implicating cytosolic calcium in flow-dependent tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…These results are consistent with the hypothesis that increased flow causes redistribution of NHE3 within the apical membrane, as found in proximal tubule cells [18]; this activation is essential for flow-stimulated Na + and HCO 3 − absorption. Finally, we have demonstrated that IP3 receptor-mediated intracellular Ca 2+ signaling plays a critical role in transduction of microvillus torque to increase Na + and HCO 3 − absorption [16]. High luminal Ca 2+ downregulates Na + and HCO 3 − absorption in the proximal tubule, and increasing Ca 2+ influx has no impact on flow-stimulated proximal tubule transport [16].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These results are consistent with the hypothesis that increased flow causes redistribution of NHE3 within the apical membrane, as found in proximal tubule cells [18]; this activation is essential for flow-stimulated Na + and HCO 3 − absorption. Finally, we have demonstrated that IP3 receptor-mediated intracellular Ca 2+ signaling plays a critical role in transduction of microvillus torque to increase Na + and HCO 3 − absorption [16]. High luminal Ca 2+ downregulates Na + and HCO 3 − absorption in the proximal tubule, and increasing Ca 2+ influx has no impact on flow-stimulated proximal tubule transport [16].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we have demonstrated that IP3 receptor-mediated intracellular Ca 2+ signaling plays a critical role in transduction of microvillus torque to increase Na + and HCO 3 − absorption [16]. High luminal Ca 2+ downregulates Na + and HCO 3 − absorption in the proximal tubule, and increasing Ca 2+ influx has no impact on flow-stimulated proximal tubule transport [16]. These results indicate that the role of Ca 2+ signals in flow regulation of Na + and HCO 3 − absorption in proximal tubule is different from its role in flow regulation of K secretion in the collecting duct [52].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations